Front-loaded (FL) microscopic approach against Conventional approach for detecting Acid Fast Bacilli (AFB) in sputum - Hossain, Mohammad Murad; Amin, Md Robed; Kabir, Ahmedul; Ahmed, Md Zobaer; Gomes, Lilian Catherene; Ahmed, Shehreen; Islam, Md Torikul (Journal of Medicine, 2019)
Introduction: Tuberculosis (TB) is one of the world’s deadliest disease. Presently, one fourth of the world’s population is thought to be infected with TB. Early diagnosis of tuberculosis is very important for therapeutic reasons and to control the spread of infection. The purpose of this study was to compare the efficacy of fluorescence (FL) microscopy in comparison to Ziehl- Neelsen (ZN) staining Methods: A cross-sectional study of 310 TB suspects attending Dhaka Medical College hospital subjected to four sputum examinations by ZN and FM. Löwenstein- Jensen culture was used as the gold standard. Of 310 suspects enrolled, 304 (98%) had a complete diagnostic work-up involving three sputum specimens for ZN and FM, culture and chest X-ray (CXR). Result: Out of 320 suspected case, 10 persons were out of our study. Among 310, 204 suspected case sputum culture was positive. Though we took sputum culture as gold standard, so there were 204 tuberculosis patient present in our study. Out of 204 TB patient 125 (61.2%) cases were positive in ZN staining. Negative ZN methods were also high 79 (39.7%) which indicate less sensitivity. On the other hand, FM methods showed 193 (94.6%) cases positive out of 204 sputum culture positive patient. It also presence of 11 cases which showed negative result in this methods. From this data we can assumed higher sensitivity of FL methods from ZN methods. Here 106 cases were culture negative. Out of these 106 people only 05 persons were positive in ZN staining whereas 10 persons were find to positive in FL methods. This message demonstrates us that specificity of ZN methods are slightly higher over FM methods. Overall sensitivity of ZN microscopic (61%)) methods are much lower than FL microscopic methods (95%). On the other hand, specificity was slightly reverse, which showed 95.5% in case ZN methods and 91% in FL methods. It also demonstrates that positive predictive value of ZN microscopy (96%) is slightly higher than FL microscopic (95%) methods but negative predictive value showed gross difference ZN microscopic (56%) and FL microscopic (89%) methods. Conclusions: The FL methods is more sensitive and shortens the diagnostic process of tuberculosis. Consequently, more patients can be put on a regimen for smear-positive TB, contributing to improved treatment and reducing transmission. For that Front-loaded (FL) microscopic approach may apply for early diagnosis and detection of tuberculosis. J MEDICINE JAN 2020; 21 (1) : 36-40